Is agritourism a driver towards sustainable farming? Evidence from Italy - Stefani, Gianluca; Benedetto, Rocchi; Defrancesco, Edi; Cei, Leonardo; Gadanakis, Yiorgos (My University, 2019)
Agritourismis increasingly perceived as a promising driver of sustainability in the development of rural economies. While the positive effects of agritourism on socio-economic sustainability of rural regions has been widely analysed much less empirical evidence has been provided on the impact of agritourist activities on environmental sustainability of farming. This study aims at providing an em-pirical assessment of the role the touristic diversification of farm activities can play as a driver towards sustainable farming. We analysed data from the Italian farm accountancy network (RICA) which provides information about both tech-nical and economic variables at farm level. We first obtained some indicators of negative environmental pressures and a measure of eco-efficiency through an application of Data envelopment analysis. We then estimated a system of equa-tions to analyse the possible determinants of environmental pressures and eco ef-ficiency including a dummy for agritourist activities of farms. Results show a certain degree of positive correlation between agritourism and sustainable prac-tices at least for fieldcrop farms while evidence is mixed for other farm types.
Keywords: Agr-tourism; sustainable agriculture; sustainable intensification; Italy; diversification